'Red' and 'white' meats—terms that lead to confusion. (1st October 2017) - Keeton, Jimmy T.; Dikeman, Michael E.
Abstract: Terms describing meat and meat products have evolved over decades to identify products originating from food animals. In general, meat is defined as skeletal muscle and associated tissues derived from commonly farmed and/or harvested mammals and, more recently, from avian and aquatic species. However, the terms "red meat" and "white meat" are a continual source of confusion due to their broad and oversimplified use in scientific publications, popular press articles, and when communicating dietary recommendations, nutrition policy, and medical advice to reduce the risk of cardiovascular disease and cancer. Therefore, this article 1) examines the origin and use of the terms "red" and "white" meats; 2) presents examples of how misuse of these terms can potentially lead to flawed conclusions; and 3) supports the need for a meat science lexicon of standardized meat terms that accurately describe "meat" and "meat product" categories.